Clues to Non-Heterosexuality: Examination of One’s Own Sexuality in Biographical Narratives (Антропологический форум / Forum for Anthropology and Culture, 2023)
This article considers how non-heterosexual people look for supposed signs of their sexual otherness in their past and display them in biographical narratives. This search for clues of a particular sort resembles an examination: the informants choose events and details from their childhood and adolescence which they suppose to be connected with their present sexual identity. Among such clues are memories of sexualised children’s games, gender otherness manifested in childhood, and a childish interest in or indifference to the topic of sexuality. Non-heterosexual people’s strategies for self-description are examined on the basis of biographical interviews and written autobiographies. Carlo Ginzburg’s evidential paradigm was chosen as an instrument of conceptualisation, but in this case it is not the researcher but the informants themselves who are engaged in the search for clues. The methodological foundation of the discussion is the biographical approach and narrative analysis. The informants used clues to non-heterosexuality discovered in their past to confirm the stability of their sexuality and at the same time to collect elements of their biographies into a single story The coherent biographical narrative allows the narrator’s non-heterosexuality to be normalised, providing an explanation and prehistory for it. At the same time, it is constructed in opposition to the heterosexual norm.